2017
DOI: 10.1111/jdv.14443
|View full text |Cite
|
Sign up to set email alerts
|

Degranulation and shrinkage of dark cells in eccrine glands and elevated serum carcinoembryonic antigen in patients with acquired idiopathic generalized anhidrosis

Abstract: Our study suggests morphological damage and molecular dysregulation of dark cells, leading to impairment of their functions in AIGA patients. Severely damaged dark cells correspond to high serum CEA. Accordingly, these pathological changes in eccrine dark cells may be involved in anhidrosis/hypohidrosis of AIGA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
1
9
2
Order By: Relevance
“…Recently, elevated serum CEA has been reported in AIGA patients, 14,18 and our previous study confirmed the increase of serum CEA in more than 60% of AIGA patients (14/22 cases) 8 . Our AIGA patients showed low frequency of high serum CEA (3/8 CEA examined cases).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Recently, elevated serum CEA has been reported in AIGA patients, 14,18 and our previous study confirmed the increase of serum CEA in more than 60% of AIGA patients (14/22 cases) 8 . Our AIGA patients showed low frequency of high serum CEA (3/8 CEA examined cases).…”
Section: Discussionsupporting
confidence: 86%
“…Previously, we reported dark cell changes such as shrinkage and degranulation at light microscopic level in AIGA patients 8 . In the current study, however, the clear cell damage revealed by electron microscopy was much more severe.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…A recent study proposed serum carcinoembryonic antigen (CEA) levels as a biomarker for the disease activity of acquired idiopathic generalized anhidrosis (AIGA) . One report showed that in AIGA patients, serum CEA is specifically elevated, relative to other adenocarcinoma tumor markers (CA19‐9 and CA125) .…”
Section: In This Study Elevated Serum Cea Has a Positive Predictive mentioning
confidence: 99%